Development of Problem-Based Learning (PBL) Teaching Materials Assisted by Wordwall in PAI Learning and Ethics of SMP Negeri 1 Tanete Luwu Regency - M. Alfath (Civiliza Publishing, Indonesia., 2026)
This study aimed to develop teaching materials for Islamic Religious Education (PAI) and Character Education using a Problem-Based Learning (PBL) approach assisted by Wordwall on the topic of compulsory prayers (salat wajib) for Grade VIII students at SMP Negeri 1 Tanete, Luwu Regency, and to determine the validity, practicality, and effectiveness of the developed materials. The study employed Research and Development (R&D) with a descriptive qualitative– quantitative approach. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research was conducted in the even semester of the 2025/2026 academic year (January–February 2026) with research subjects consisting of a content expert, a media expert, and 23 Grade VIII students (14 female and 9 male). Data were collected through observation, expert validation, student response questionnaires, and a learning achievement test. Data were analyzed descriptively using quantitative techniques (mean scores and percentages) and qualitative descriptions based on validators’ suggestions and student feedback. The results showed that the teaching materials were categorized as highly feasible based on content expert validation with an average score of 4.67 and media expert validation with an average score of 4.60. In terms of practicality, the student response questionnaire produced an average score of 3.65, categorized as highly practical. The effectiveness of the materials was indicated by postimplementation learning outcomes: 20 out of 23 students (86.96%) achieved scores ≥ the Minimum Mastery Criterion (KKM) of 75, thus meeting the effectiveness criterion (≥75% mastery). Therefore, the PBL-based teaching materials assisted by Wordwall were concluded to be highly feasible, highly practical, and effective for use in PAI and Character Education learning for Grade VIII students at SMP Negeri 1 Tanete, Luwu Regency.